2012
DOI: 10.1080/19768354.2012.680495
|View full text |Cite
|
Sign up to set email alerts
|

The role of ginseng total saponin in transient receptor potential melastatin type 7 channels

Abstract: Although ginsenosides have a variety of physiologic or pharmacologic functions in various regions, there are only a few reports on the effects of transient receptor potential melastatin 7 (TRPM7) channels. Here, we showed evidence suggesting that TRPM7 channels play an important role in ginseng total saponin (GTS)-mediated cellular injury. The combination techniques of electrophysiology, pharmacological analysis, small interfering RNA (siRNA) method and cell death assays were used. GTS depolarized the resting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The pacemaker activity of ICCs in the murine small intestine occurs primarily because of periodic activations of TRPM7 [16] or ANO1 channels [20] . Ginsenoside Rf has no effects on TRPM7 or ANO1 channels [3] , but GTS and ginsenoside Rg3 block TRPM7 channels [40] , [41] . However, the specific details of ion channel involvement during the upstroke and plateau phases of pacemaker potentials in the presence of GRe have not been elucidated.…”
Section: Discussionmentioning
confidence: 98%
“…The pacemaker activity of ICCs in the murine small intestine occurs primarily because of periodic activations of TRPM7 [16] or ANO1 channels [20] . Ginsenoside Rf has no effects on TRPM7 or ANO1 channels [3] , but GTS and ginsenoside Rg3 block TRPM7 channels [40] , [41] . However, the specific details of ion channel involvement during the upstroke and plateau phases of pacemaker potentials in the presence of GRe have not been elucidated.…”
Section: Discussionmentioning
confidence: 98%
“…Meyer and a well-known folk medicine and tonic), ginseng total saponin (GTS) 61 and ginsenosides Rg3 62 and Rd 63 were found to induce AGS cell death by blockading TRPM7 channel activity. Thus, these results suggested that TRPM7 channels are involved in GTS, ginsenoside Rg3, and Rd-induced gastric cancer cell apoptosis.…”
Section: Trpm7 Channels and Gastric Cancermentioning
confidence: 99%
“…Ginseng is one of the most popular herbal remedies and contains ginsenosides, also known as steroid-like saponins known for activating antioxidant enzymes. A study has suggested that ginsenosides cause cellular injury by damaging the DNA and causing endoplasmic reticulum (ER) stress (18). More specifically, ginsenoside Rd has the ability to inhibit TRPM7 channels that were overexpressed in kidney cells and human gastric adenocarcinoma cells as well as inhibit the phosphorylation of the MAPK pathway (18).…”
Section: Introductionmentioning
confidence: 99%
“…A study has suggested that ginsenosides cause cellular injury by damaging the DNA and causing endoplasmic reticulum (ER) stress (18). More specifically, ginsenoside Rd has the ability to inhibit TRPM7 channels that were overexpressed in kidney cells and human gastric adenocarcinoma cells as well as inhibit the phosphorylation of the MAPK pathway (18). Because of its role as a magnesium transporter, TRPM7 is essential for magnesium-dependent cell survival of gastric cancer cells and is also involved in apoptosis caused by ginsenosides, steroid-like saponins in ginseng, like ginsenoside Rd (9).…”
Section: Introductionmentioning
confidence: 99%